EFFECTIVENESS OF GUTTER FUND-BASED BOS FUNDS UTILIZATION AT PUBLIC ELEMENTARY SCHOOL 2 BUDIASIH - Eneng Eva Sundari; Risbon Sianturi; Sophia Choirotul Husniyyah; Dian Sudiana; Nisa Ul (Jurnal Cakrawala Pendas, 2023)
Finances in an educational unit must be properly managed. It is important to participate in contributing to school funds so that the funds received function effectively and efficiently. The use of BOS or funds needs to be based on agreements and conclusions with the managers of these BOS funds, teachers and school institutions. Based on the results of the agreement, it is submitted in the form of written minutes of the meeting and signed by all meeting participants. In fact there were several obstacles that occurred including the ineffectiveness of school financial management, no staff who were proficient in managing school finances, delays in the disbursement of BOS funds. The purpose of this study was to describe the effectiveness of the use of BOS funds at SDN 2 Budiasih. The method used in this research is qualitative, with a field case study research design with descriptive-analytic characteristics. In collecting data using techniques for collecting this data will use, by way of interviews, documentation and observation. The results obtained from this study are that there is often a delay in the allocation of funds at SD Negeri 2 Budiasih which has an impact on learning activities at the school. If there is a delay in the distribution of school operational funds, the school's needs will become more difficult. Evaluation must be carried out so that school operational assistance funds are distributed on time with the right calculation in achieving all school activities and needs so that school operational activities run well and do not interfere with the school program that has been planned. Finansial di salah satu satuan pendidikan harus ditata dengan baik. Penting untuk ikut serta memberikan kontribusi dana sekolah agar dana yang diterima berfungsi selaku efektif dan efisien. Penggunaan BOS atau dana perlu berlandaskan persetujuan serta kesimpulan bersama pengelola dalam dana BOS ini, pihak guru serta lembaga sekolah. Berdasarkan hasil persetujuan disampaikan pada bentuk risalah rapat tertulis serta di tanda tangani seluruh peserta rapat. Penelitian ini merupakan jenis metode kualitatif akan memerlukan desain terhadap penelitian studi kasus lapangan dengan berkarakter deskriptif-analitik. Pada pengambilan data mengunakan teknik terhadap pengumpulan data ini akan mengunakan, dengan cara wawancara, dokumentasi serta observasi. Inilah dapat ditunjukkan oleh hasil pada penelitian ini dengan menunjukkan bahwa seringnya terjadi keterlambatan alokasi dana di SD Negeri 2 Budiasih berdampak pada kegiatan pembelajaran di sekolah tersebut. Jika terjadi keterlambatan penyaluran dana operasional sekolah, kebutuhan sekolah menjadi lebih sulit. Evaluasi harus dilakukan agar dana bantuan operasional sekolah tersalurkan tepat waktu dengan perhitungan yang tepat dalam mencapai semua kegiatan dan kebutuhan sekolah.